Colorectal Cancer Chemoprevention by Mesalazine and Its Derivatives - Stolfi, Carmine (Hindawi Publishing Corporation, 2012)
Patients with inflammatory bowel disease (IBD) face an increased lifetime risk of developing colorectal cancer (CRC). Independent factors associated with increased risk include long disease duration, extensive colonic involvement, young age at onset of IBD, severity of inflammation, primary sclerosing cholangitis, backwash ileitis, and a family history of CRC, thus emphasising the role of intestinal inflammation as an underlying mechanism. This notion is also supported by the demonstration that the use of certain drugs used to attenuate the ongoing mucosal inflammation, such as mesalazine, seems to associate with a reduced incidence of colitis-associated CRC. In the last decade, work from many laboratories has contributed to delineate the mechanisms by which mesalazine alters CRC cell behaviour. In this paper, we review the available experimental data supporting the ability of mesalazine and its derivatives to interfere with intracellular signals involved in CRC cell growth.